Comparing the automatic evaluation of CPR compression rates using a smartwatch vs a smartphone - Dawson-Howe, Kenneth; D'Art, Senan (My University, 2021)
This paper presents a novel algorithm for automatically evaluating the compression rate for Cardio Pulmonary Resucitation (CPR) from the sensor data from a smartwatch. The results are compared with manually derived ground truth and with the results of an automatic system based on the analysis of video from a smartphone.
Irish Machine Vision and Image Processing Conference
Keywords: Image processing; CPR; Motion analysis; Computer Vision; mobile apps